If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -8m = 2m + 2 Reorder the terms: 12 + -8m = 2 + 2m Solving 12 + -8m = 2 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. 12 + -8m + -2m = 2 + 2m + -2m Combine like terms: -8m + -2m = -10m 12 + -10m = 2 + 2m + -2m Combine like terms: 2m + -2m = 0 12 + -10m = 2 + 0 12 + -10m = 2 Add '-12' to each side of the equation. 12 + -12 + -10m = 2 + -12 Combine like terms: 12 + -12 = 0 0 + -10m = 2 + -12 -10m = 2 + -12 Combine like terms: 2 + -12 = -10 -10m = -10 Divide each side by '-10'. m = 1 Simplifying m = 1
| 14-(2q+5)=(-2q)+9 | | -3/4x+5/4=x+3 | | 12x+4/4(x-1)(x+1)=5/4 | | 8x-16=4(2x-4) | | 22=4+3t | | x+30=93 | | -1/4y+5/4=-5/6y+5/3 | | -42=14y | | .2x-3=1 | | -5(9r+10)+5r=10(r+10) | | 2.2x-3=1 | | 3r^2+10r-4=84 | | 9-3(9z+1)=-4(-z-6)-8 | | x^3-19x=-30 | | 15=5/9(f-32) | | -2y+20=-5y+5 | | 300-20x=150+20x | | 3.7+3.25x= | | 11x-31=90 | | 21-1/24(3x)=14-1/24(2x) | | 4x6/11 | | 8x+42=90 | | -n+8.5=14.4 | | -2+8(n-3)=2(-9n-5)+7 | | 2x^2-38x=0 | | 2x+5=10y | | 3u-14=-6u-5 | | (3h-1)(h+5)= | | 25x^2+10x-24=0 | | -2.3(m-1.1)-4.6=-13.57 | | 5x-30=90 | | 4x-27=7x |